Influence a Realistic Mathematics Education Approach and Motivation on Students' Mathematical Reasoning Ability - A. M. Mega Purnamatati; Herlina Usman; Elih Yunianingsih (Journal of Instructional Mathematics, 2023)
The purpose of the research was to provide knowledge of the effect of the Realistic Mathematics Education (RME) approach and motivation on students' mathematical reasoning abilities. This quasi-experimental study employed a pretest-posttest control group design, focusing on fifth-grade students at SDN Lulut 05, Klapanunggal District. Class VA was selected as the experimental group, while class VB served as the control group using purposive sampling. Data analysis involved the N-gain formula and t-test. The results shown: (1) There is a difference in the increase in students' mathematical reasoning ability after being given the RME approach indicated by the N-gain value of 55.5 in the medium category and for the experimental class 36.8 in the low category, then the control class in the t-test (independent) so that the Sig value is obtained. 0.001<0.005, as for deciding in the independent sample t-test. It is concluded that there is a significant difference between the average score mathematical reasoning ability by students treated with the RME approach and the Conventional approach. (2) There is an influence of the RME approach on students' mathematical reasoning abilities with an effect size score of 1.44 which is in the high category.